Development and evaluation of the clinimetric properties of the Medication-Related Osteonecrosis of the Jaw Quality of Life Questionnaire (MRONJ-QoL). Issue 6 (June 2022) - El-Rabbany, M.; Blanas, N.; Sutherland, S.; Shah, P.S.; Lam, D.K.; Azarpazhooh, A.
Abstract: The purpose of this study was to develop a self-administered questionnaire (MRONJ-QoL) to assess the quality of life (QoL) of patients with medication-related osteonecrosis of the jaw (MRONJ). A prospective study was performed to develop and evaluate the questionnaire. The MRONJ-QoL was formulated through a review of the literature and interviews of experts and patients. Following development, it was administered to 60 patients with a diagnosis of MRONJ. The sensibility of the questionnaire was assessed by evaluating feasibility (via interviews of patients), face validity (via interviews of patients and experts), and content validity (via evaluation of internal consistency, floor/ceiling effects, and factor analysis). Reliability was evaluated by measuring intra-rater reliability. Construct validity of the questionnaire was evaluated by both cross-sectional and longitudinal comparisons, including comparing scores of the MRONJ-QoL to disease resolution at 6 months. The final MRONJ-QoL questionnaire consisted of 14 questions, demonstrating high internal consistency (Cronbach's alpha of 0.85) and good reliability (weighted kappa score of 0.65). At the 6-month follow-up, disease resolution was found to be significantly associated with improved MRONJ-QoL scores, suggesting validity of the questionnaire ( P < 0.01). Therefore, this is a sensible, reliable, and valid questionnaire for evaluating the QoL of patients with MRONJ.